Effect of vermicompost and fertilizer on uptake and efficiency of nutrients in pot culture rice - Kumar Chiranjeeb; S. S. Prasad; Vivek Kumar; Rajani K.; Munmun Majhi; Megha Bhadani (Environment Conservation Journal, 2022)
Rice is the major dominant crop in the asian continent and all over the world. A research was carried out at Dr. Rajendra Prasad Central Agricultural University, Pusa in kharif, 2018 containing four different levels of vermicompost (0 t/ ha , 1.25 t/ ha, 2.5 t/ ha, 3.7 t/ ha) and three levels (0 %, 100 %, 50 % Recommended Dose of Fertilizer) of fertilizer RDF were combined with each other and analyzed for nutrient uptake and efficiencies in pot cultured rice crop variety Rajendra Bhagawati.  Study revealed that nutrient uptake in grain (446.03 mg/ pot N, 104.95 mg/ pot P , 112.06 mg/ pot K) and straw (303.81 mg/ pot N , 49.83 mg/ pot P, 578.78 mg/ pot K) and the total nutrient uptake i.e. N (227.67 mg/ pot ), P(0.083 mg/ pot ), K(690.84 mg/ pot) were superior in the combined application of 3.75 t/ ha vermicompost and 100% RDF over other and showed higher stability in case of apparent nutrient use efficiency in 3.75 t/ ha vermicompost and 50% RDF except potassium for balanced growth of rice crop and declining straight 50% cost off chemical fertilizer substituted with organic sources.